Problems, Suggestions and Last Trends Related to Salgam Beverage which is Traditional Product of Turkey - Hasan Tangüler; Selin Özge Dinç; Sermet Can Beylikci (Turkish Journal of Agriculture: Food Science and Technology)
Salgam (Şalgam, shalgam) is our conventional fermented purple carrot beverage. Purple carrot (Daucus carota) is the basic raw material, and other raw materials used in the production are sourdough/ bakers’ yeast, salt (rock), bulgur flour and/or turnip (Brassica rapa L.). There are two fermentations that occur due to microorganisms (lactic-acid bacteria and yeast) that are effective during production; primarily lactic-acid fermentation and ethyl alcohol fermentation. It is very popular in our country, especially southerly cities of Turkey. Although shalgam is mostly produced and consumed in Mersin/İcel, Osmaniye, Hatay-Antakya and Kahramanmaras cities, the most known and loved city is the Adana. Lately, it has begun to be consumed almost every parts of Turkey. In addition, it is sold in the cities where the densities of the Turks in Europe. The aim of this review article is to give information about the production methods of salgam, scientific studies and recent trends, problems related to salgam and solutions.